Total elbow arthroplasty for acute distal humeral fractures in patients over 65 years old – Results of a multicenter study in 87 patients - Mansat, P.; Nouaille Degorce, H.; Bonnevialle, N.; Demezon, H.; Fabre, T. (Orthopaedics & traumatology, surgery & research, 2013)
Fractures of the distal humerus represent 5% of osteoporosis fragility fractures in subjects over the age of 60. Osteoporosis, comorbidities and intra-articular comminution make management of this entity difficult. The hypothesis was that total elbow arthroplasty could be a reliable treatment option in subjects over the age of 65 presenting with a fracture of the distal humerus. Eight-seven patients (80 women and 7 men) mean age 79 years old (65–93) underwent total elbow arthroplasty for the treatment of an AO type A fracture in 9 cases, type B in 8 and type C in 70. After a mean follow-up of 37.5 months (6–106) the Mayo Elbow Performance Score MEPS was 86±14, the quick-DASH score was 24±19 and the Katz score was 5±1.5 points. The MEPS was better in patients with a high preoperative Katz score and a history of inflammatory arthritis who were living at home. Fifty-five patients (63%) presented with a pain-free elbow, and 20 (24%) with slight pain. The flexion-extension range of motion was 97±22° and 48% presented with a flexion-extension arc of at least 100°. Function was normal in 69 patients. Complications were identified in 20 cases (23%) and revision surgery was necessary in 8 (9%). Two arthroplasties had to be changed, one for a fracture of the humeral stem component and the other for loosening. Only one infection occurred in this series. Total elbow arthroplasties provide fractured patients with immediate satisfactory results and a stable, painless and functional elbow. These results seem to be reliable and durable. The rate of complications is low with revision surgery in approximately 10%. Level IV.